Across and Beyond the Far Left: The Case of Gilles Dauvé. Issue 2 (2nd April 2016) - el-Ojeili, Chamsy; Taylor, Dylan
Abstract : This essay explores the work of French ultraleftist Gilles Dauvé. Situating his contribution against a discussion of left communism as a unified intellectual-political current, it identifies and discusses three crucial moments in Dauvé's work. A first moment, 1969–1979, sees Dauvé attempting to critically draw together council communist, Bordigist, and situationist contentions into a unified and unique communist perspective. During a second moment, coincident with the crisis of Marxism, Dauvé continued to solidify this position, in particular criticizing the confluence of liberal-democratic thought with antifascism. In a third moment, 1999–present, Dauvé has engaged in important rethinking and clarification, further underscoring communism as communization. The essay's conclusion underscores the importance of Dauvé's singular intellectual journey in terms of its novel synthetic quality, its resonance with contemporary discussions of the appearance of a new global Left, and its important contribution to the communization current.